The risk of death in running road races - Frere, J. A.; Maharam, L. G.; van Camp, S. P. (The Physician and Sportsmedicine, 2004)
BACKGROUND: Although the risk of death for marathon participants and for high school and college athletes has been quantified, limited data are available about the risk of death in running shorter road races. OBJECTIVE: To determine the incidence and causes of exercise-related death in running road races and to provide information that may help identify those at risk and assist race directors with medical staffing needs. METHODS: Investigators requested the number of finishers and the number of deaths within a 5-year period (1996 through 2000) from 62 of the largest races (according to USA Track and Field in 1999) from 10K, 12K, 15K, and half-marathon distances. Differences in the risk of death between these races and marathons were compared with a chi-square analysis. RESULTS: Thirty-eight (61%) of the officials from the 62 races responded. Five deaths occurred among 1,636,720 finishers. All the fatalities were men, and their age range was wide (38 to 84 years). Most of the deaths were in 10K races (4 deaths); 1 was in a half-marathon race. Further data were available on 3 of the runners, whose deaths were attributed to coronary artery disease. The overall incidence of death in running road races was approximately 3.1 per 1 million finishers. This risk and that for 10K races are significantly lower than the risk reported for marathons from combined data from other sources. CONCLUSION: The risk of death in running road races is significantly lower than the risk for marathons. These data may help to identify participants at risk and assist race directors in determining medical staffing needs on race day.